2022
DOI: 10.3390/w14050709
|View full text |Cite
|
Sign up to set email alerts
|

Multistage Models for Flood Control by Gated Spillway: Application to Karkheh Dam

Abstract: The paper demonstrates a simulation optimization framework for enhancing the real-time flood control with gated spillways at places where no flood forecasting data are available. A multiobjective modeling scheme is presented for the flood management in a gated spillway in which the operator may specify the priorities on floods based on their different return periods. Two different operation strategies were devised. Both operating strategies employ ten-stage policies, which rely on the reservoir water level as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…For example, the study by (Sajedi Hosseini et al, 2021) examines the impact of dam construction on flood attenuation in the Karkheh River basin, Iran, highlighting the ability of the dam to store excess water during flood events. However, reservoir operation strategies are crucial in optimizing flood control measures (Salehi et al, 2022;Su et al, 2022;Yu et al, 2023). Furthermore, the benefits and drawbacks of dams and retention basins in flood control should be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the study by (Sajedi Hosseini et al, 2021) examines the impact of dam construction on flood attenuation in the Karkheh River basin, Iran, highlighting the ability of the dam to store excess water during flood events. However, reservoir operation strategies are crucial in optimizing flood control measures (Salehi et al, 2022;Su et al, 2022;Yu et al, 2023). Furthermore, the benefits and drawbacks of dams and retention basins in flood control should be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the roulette-wheel selection method is employed to select generations in the reproduction process of the genetic algorithm. In this method, the probability of selecting a string or chromosome is proportional to its fitness (Salehi et al, 2022). The genetic algorithm starts the search using an initial set of random solutions, and it can perform multiple searches and iterations over a population of variables, increasing the likelihood of finding a global optimal solution.…”
Section: Fig 3 Flow Chart Of Genetic Algorithmmentioning
confidence: 99%
“…Thus, in the absence of irrigation canals, the water continues to flow to Iran without restriction. 70 In addition, the Islamic Emirate of Afghanistan under the Taliban's administration recently released water from the Helmand River to the Sistan-Baluchistan region after water in the Kamal Khan reservoir reached its maximum level. 71 Hence, despite the existence of an international water treaty for the Helmand River, the basin continues to suffer from water disputes between the upstream and downstream riparian states 40,45,64,66 as a result of the adverse impacts of climate changes (p 2) 68 and water scarcity due to an increase in population and agricultural activity.…”
Section: Historical Contextmentioning
confidence: 99%
“…While the dam was inaugurated on March 24, 2021, 14,69 the Hamoun Helmand was already desiccated by 2000 (p 356). 68 Also, Jain 30 and Salehi 70 concluded that despite the inauguration of Kamal Khan Dam, farmers in Nimroz province, the province in which Kamal Khan Dam is located, still face a water crisis as the Afghan government has not yet constructed the related irrigation canals. Thus, in the absence of irrigation canals, the water continues to flow to Iran without restriction.…”
Section: Historical Contextmentioning
confidence: 99%